2022
DOI: 10.1177/10790632221139178
|View full text |Cite
|
Sign up to set email alerts
|

Do Sanctions Affect Undetected Sexual Offending?

Abstract: Undetected sexual offending creates challenges for risk assessment since estimated sexual recidivism rates are based on documented charges or convictions. Courts and other stakeholders may be primarily interested in the true risk for sexual reoffense and not simply risk for detected sexual offenses. Attempts to study and quantify the rate of undetected sexual offending have resulted in a wide variety of estimates. In this study, we explore whether sanctions imposed for detected sexual offenses increase the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…First, because the under‐reporting of sexual offenses is a universal problem, it is uncertain whether the nonrepeat offenders in this study were truly first‐time offenders. Undetected sex offenders are not uncommon, posing significant challenges for risk assessment (Kelley et al., 2023; Lisak & Miller, 2002). Furthermore, given the difficulty of obtaining official crime data in mainland China (see Chan, Li, Liu, Lu, et al., 2019) and the inaccessibility of official crime data on sexual homicides, only basic descriptive information about the offenders, victims, and MO characteristics could be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…First, because the under‐reporting of sexual offenses is a universal problem, it is uncertain whether the nonrepeat offenders in this study were truly first‐time offenders. Undetected sex offenders are not uncommon, posing significant challenges for risk assessment (Kelley et al., 2023; Lisak & Miller, 2002). Furthermore, given the difficulty of obtaining official crime data in mainland China (see Chan, Li, Liu, Lu, et al., 2019) and the inaccessibility of official crime data on sexual homicides, only basic descriptive information about the offenders, victims, and MO characteristics could be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these men in the Dunkelfeld project, however, had never been detected by the criminal justice system, and their behavior may be different compared with men who have been caught and sanctioned for their offending. For example, Kelley et al (2023) found that the number of undetected sex offenses decreased after the first sanction for sexual offending. A recent study on men convicted for CSEM offenses found that 10% self-reported reoffending under anonymous survey conditions (Steel et al, 2021).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%